StandardEssential Patents and Antitrust – Patent-Protected Technologies Remain a Key Contributor to Innovation and Competitiveness in the European Union? - Viitanen, Emmi (fi=Turun yliopisto|en=University of Turku|, 2017)
The importance of standardization based on patented technologies to the industrial innovation and competitiveness of the EU has been increasingly recognized by the EU institutions. The European Commission for example stated in its staff working document Advancing the Internet of Things in Europe of 2016 that standardization is the critical element to deliver a single market for internet of things (IoT). Furthermore, it has been stated by the European Commission that standards are one of the cornerstones of the Digital Single Market. Efficient licensing of standard essential patents (SEP) in turn, is the key to the success of a standard. Competition law and policy have a variety of different purposes. One leading premise of this study is that competition policy aims at promoting public welfare that strives from technological development. Although standard-setting has generally been seen beneficial to the public, it may still pose problems from the perspective of Article 102 of the TFEU. This study is concerned with SEP holders´ conduct, in particular the SEP owner’s possibility to negotiate the license terms on the use of their SEP and ultimately seek injunction if their SEP has been implemented without license. In this context, an interesting question of when does the IP owner become IP abuser, will be investigated. This study adopts the legal-dogmatic method, in addition to which law and economics is utilized to establish that standard technology patents are still key players in the technology development, thus the improvement of public welfare, which is why they should be further promoted by the legislative and regulatory environment in the EU. As regards SEPs, the general concern has been that the holders of SEPs included in the standard may start to behave in anti-competitive way e.g. by refusing to license on FRAND terms. This study seeks to investigate into the question of is it a patent hold-out that is the problem of today rather than a patent hold-up. Although IP rights are recognized as efficient competition tools, they may also restrict the efficient competition in the form of exclusive rights. Yet, it can be argued that the tension between the two norms is rather apparent than real as technology development is the shared purpose of both IP and antitrust laws. In addition, following the Court of Justice of the EU’s ruling in Case C-170/13 (Huawei) in 2015, it seems that the regulatory environment in the EU has become more favorable to the SEP owners.